Alat Bukti Yang Paling Kuat Dalam Proses Peradilan di Pengadilan Agama - Rahmadani, Gema; Hamdani, Muhammad Faisal; Yuslem, Nawir (Universitas Medan Area, 2023)
The purpose of this study is to analyze a strong evidence in the judicial process in the Religious Court which the strongest evidence will be accepted by the judge. In the trial the parties put forward events that can. In civil law the strongest evidence is written evidence, whereas in Islamic law written evidence is not very popular or has not been considered the strongest, but confession and oath evidence are considered strong evidence. This type of research uses normative legal research, using a conceptual approach and a statutory approach. Types and sources of legal materials are positive law, Islamic law and the Qur'an and hadith, primary and secondary. Legal materials obtained and analyzed qualitatively and then presented descriptively. The results of this study explain that acceptable evidence that is considered the strongest according to the Qur'an is an oath, while in civil law the strongest evidence is written.